Progress in partial least squares structural equation modeling use in marketing research in the last decade - Marko Sarstedt; Joseph F. Hair; Mandy Pick; Benjamin D. Liengaard; Lăcrămioara Radomir; Christian M. Ringle (Psychology & Marketing, 2022)
Partial least squares structural equation modeling (PLS-SEM) is an essential element of marketing researchers' methodological toolbox. During the last decade, the PLS-SEM field has undergone massive developments, raising the question of whether the method's users are following the most recent best practice guidelines. Extending prior research in the field, this paper presents the results of a new analysis of PLS-SEM use in marketing research, focusing on articles published between 2011 and 2020 in the top 30 marketing journals. While researchers were more aware of the when's and how's of PLS-SEM use during the period studied, we find that there continues to be some delay in the adoption of model evaluation's best practices. Based on our review results, we provide recommendations for future PLS-SEM use, offer guidelines for the method's application, and identify areas of further research interest.
Keywords: 650; marketing models; partial least squares; PLS-SEM; research methodology; SEM; structural equation modeling